Molecular identification of Mucorales in human tissues: contribution of PCR electrospray-ionization mass spectrometry. (June 2015) - Alanio, A.; Garcia-Hermoso, D.; Mercier-Delarue, S.; Lanternier, F.; Gits-Muselli, M.; Menotti, J.; Denis, B.; Bergeron, A.; Legrand, M.; Lortholary, O.; Bretagne, S.; ,
Abstract: Molecular methods are crucial for mucormycosis diagnosis because cultures are frequently negative, even if microscopy suggests the presence of hyphae in tissues. We assessed PCR/electrospray-ionization mass spectrometry (PCR/ESI-MS) for Mucorales identification in 19 unfixed tissue samples from 13 patients with proven or probable mucormycosis and compared the results with culture, quantitative real-time PCR, 16S–23S rRNA gene internal transcribed spacer region (ITS PCR) and 18S PCR sequencing. Concordance with culture identification to both genus and species levels was higher for PCR/ESI-MS than for the other techniques. Thus, PCR/ESI-MS is suitable for Mucorales identification, within 6 hours, for tissue samples for which microscopy results suggest the presence of hyphae.